Increased Gamma Connectivity in the Human Prefrontal Cortex during the Bereitschaftspotential - Kim, Kisun; Kim, June Sic; Chung, Chun Kee (Frontiers in Human Neuroscience, 2017)
The Bereitschaftspotential (BP) is a slow negative cortical potential preceding voluntary movement. Since movement preparation is dependent upon the synchronous activity of a variety of neurons, BP may develop through the exchange of information among motor-related neurons. However, the relationship between BP and information flow is not yet well-known. In the present study, we aimed to investigate how the connectivity in the prefrontal cortex (PFC) changes during the occurrence of BP. Electrocorticography (ECoG) was recorded in 5 patients with epilepsy. The subjects performed self-paced hand grasping. We compared the intraregional connectivity between PFC and non-PFC regions using partial directed coherence. In the PFC, the connectivity of beta and gamma bands in the BP period increased by an average of 24.4% compared with the baseline connectivity. Conversely, gamma connectivity in non-PFC regions decreased by 31.4%. Moreover, the intraregional connectivity in the PFC increased according to the stage of BP. The increased gamma band connectivity in the PFC implies that the increased communication among neurons in the PFC is associated with development of BP. Intraregional connectivity as one of the factors involved in voluntary movement may reflect the activation of brain networks related to movement preparation in PFC.